Diatom communities of high-altitude creeks in Bosnia and Herzegovina - Dedić Anita; Kapetanović Tatjana; Hafner Dubravka; Barinova Sophia (Oceanological and Hydrobiological Studies)
Diatoms from two high-altitude creeks in Bosnia and Herzegovina were studied from June 2005 to May 2007. Along with diatoms, water temperature, pH, conductivity and nutrients were also monitored, indicating stable physical and chemical conditions, low organic loading and oligotrophy. A total of 130 diatom taxa (species and subspecies) were recorded. Mostly oligotrophic and oligo-mesotrophic indicators were recorded in the creeks. The most abundant genera were Eunotia (15), Pinnularia (13), Gomphonema (10) and Navicula (9). The following taxa were recorded in all samples: Cymbopleura naviculiformis (Auerswald ex Heiberg) Krammer, Decussiphycus hexagonus (Torka) Guiry & Gandhi, Eunotia arcus Ehrenberg, Frustulia vulgaris (Thwaites) De Toni, Pinnularia borealis Ehrenberg and Pinnularia viridis (Nitzsch) Ehrenberg. Five new diatom taxa for Bosnia and Herzegovina were recorded. According to the German Red List, the largest number of taxa (34 for creek 1 and 27 for creek 2) were identified as declining taxa and 12 taxa as endangered ones (three for creek 1 and nine for creek 2). The high species richness and the presence of diatom taxa included on the German Red List underline the importance of protecting and preserving this important biotope.